The Influence of Cashless Society, Lifestyle, and Financial Literacy on the Consumptive Behavior of Students in Kediri City - Friska Resty Fandya; Angga Rizka Lidiawan; Dita Riyanto Putro (CV. Civiliza Publishing, 2026)
The purpose of this study is to examine and evaluate how a cashless society, lifestyle, and financial literacy affect Kediri City students' purchasing habits. Using an explanatory design and a quantitative research approach, the population consisted of Kediri City university students who regularly use non-cash payment methods. Purposive sampling, a non-probability sampling approach, was used, resulting in a sample size of 100 respondents. Likert scale-based questionnaires were used to collect data. With the use of the SmartPLS software, SEM-PLS analysis was used to test hypotheses. The findings indicate that “the concept of a Cashless Society exerts a positive and statistically significant influence on student consumer behavior”. Similarly, Lifestyle demonstrates a significant and positive effect, while Financial Literacy also significantly impacts consumer behavior among students in Kediri City.